Novels for students. presenting analysis, context, and criticism on commonly studied novels - Constantakis, Sara; Devereaux, Jordan (Gale virtual reference library, 2012)
Provides critical overviews of novels from various cultures and time periods. Includes discussions of plot, characters, themes and structure as well as the work's cultural and historical significance.